2009
DOI: 10.1007/s11099-009-0043-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes of photosynthetic activities of maize (Zea mays L.) seedlings in response to cadmium stress

Abstract: Maize (Zea mays L.) seedlings were grown in nutrient solution culture containing 0, 5, and 20 µM cadmium (Cd) and the effects on various aspects of photosynthesis were investigated after 24, 48, 96 and 168 h of Cd treatments. Photosynthetic rate (P N ) decreased after 48 h of 20 µM Cd and 96 h of 5µM Cd addition, respectively. Chl a and total Chl content in leaves declined under 48 h of Cd exposure. Chl b content decreased on extending the period of Cd exposure to 96 h. The maximum quantum efficiency and poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 45 publications
5
30
0
Order By: Relevance
“…Along with the entire group of unfavorable aspects of Cd on the rhizosphere (Lux et al, 2011), several toxicity reports of Cd on the cell level (Benavides et al, 2005;Martinka et al, 2014), as well as negative influence of this heavy metal on photosynthetic-related processes in leaf mesophyll tissues are known (Hasan et al, 2009). In maize, Cd was shown to decrease the chlorophyll synthesis (Lagriffoul et al, 1998;Chaneva et al, 2010), effective photochemical quantum yield of photosystem II (Φ PSiI ), as well as rate of CO 2 fixation (Ekmekçi et al, 2008;Wang et al, 2009;Da Silva et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Along with the entire group of unfavorable aspects of Cd on the rhizosphere (Lux et al, 2011), several toxicity reports of Cd on the cell level (Benavides et al, 2005;Martinka et al, 2014), as well as negative influence of this heavy metal on photosynthetic-related processes in leaf mesophyll tissues are known (Hasan et al, 2009). In maize, Cd was shown to decrease the chlorophyll synthesis (Lagriffoul et al, 1998;Chaneva et al, 2010), effective photochemical quantum yield of photosystem II (Φ PSiI ), as well as rate of CO 2 fixation (Ekmekçi et al, 2008;Wang et al, 2009;Da Silva et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction may be attributed to the reduced stomatal pore size, induced lower CO 2 assimilation and lowered photosynthetic rate under the condition of stress (Ali et al 1999). Photosynthesis is, in fact, one of the foremost processes to be affected by Cd treatment (Wang et al 2009). The decline in photosynthesis can be attributed to low stomatal conductance as was observed in Acer leaves, which have small stomatal apertures (Jensen & Kozlowski 1975).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the application of phosphate fertilizers decreased the mobility of Cd in soil by changing mobile forms of Cd to the immobile form of Cd phosphate. The other mechanism shown for decreasing Cd stress is by the addition of P and increasing GSH content and prevented membrane damage [62]. Similarly, improving K nutrition of plants under stress has been shown to minimize the oxidative cell damage by reducing ROS formation during photosynthesis and inhibiting activation of oxygen radical generating NADPH oxidase [63] and the form of K applied plays a significant interaction with Cd in plants.…”
Section: Macro Nutrientsmentioning
confidence: 99%